2020
DOI: 10.3390/rs13010088
|View full text |Cite
|
Sign up to set email alerts
|

Solar Brightening/Dimming over China’s Mainland: Effects of Atmospheric Aerosols, Anthropogenic Emissions, and Meteorological Conditions

Abstract: Surface solar radiation (SSR) is the main factor affecting the earth’s climate and environment and its variations and the reason for these variations are an important part of climate change research. In this research, we investigated the long-term variations of SSR during 1984–2016 and the quantitative influences of atmospheric aerosols, anthropogenic emissions, and meteorological conditions on SSR over China’s mainland. The results show the following: (1) The annual average SSR values had a decline trend at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Fu et al (2020) found that annual total Nr deposition increased at a rate of 10%, and the ground‐level O 3 and NH 3 concentrations also increased by 13% and 107% during 2011–2018 in this region, respectively. Thus, the increased aerosol loading was also the main driving factor for dimming in Northwest China, which has also been proven by Fang et al (2021). Presumably, it is not easy for weaker winds to blow away aerosols, thus causing more aerosols to remain in the atmosphere (Glantz et al, 2009; Kiliyanpilakkil & Meskhidze, 2011; Yackerson, 2002).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Fu et al (2020) found that annual total Nr deposition increased at a rate of 10%, and the ground‐level O 3 and NH 3 concentrations also increased by 13% and 107% during 2011–2018 in this region, respectively. Thus, the increased aerosol loading was also the main driving factor for dimming in Northwest China, which has also been proven by Fang et al (2021). Presumably, it is not easy for weaker winds to blow away aerosols, thus causing more aerosols to remain in the atmosphere (Glantz et al, 2009; Kiliyanpilakkil & Meskhidze, 2011; Yackerson, 2002).…”
Section: Discussionsupporting
confidence: 66%
“…by Fang et al (2021). Presumably, it is not easy for weaker winds to blow away aerosols, thus causing more aerosols to remain in the atmosphere (Glantz et al, 2009;Kiliyanpilakkil & Meskhidze, 2011;Yackerson, 2002).…”
Section: Possible Reasons For the Dominant Role Of Interaction Betwee...mentioning
confidence: 99%
“…Mongolia and Russia have low AOD values due to their high latitude, alpine terrain, and sparse population under both small natural and anthropogenic influences. Qinghai Province and Tibet Autonomous Region are located in the Qinghai-Tibet Plateau with high altitude, low human activities, and thin atmosphere [54], thus the AOD values are extremely low. Most of the AOD in East Asia show a significant negative trend, indicating that aerosol pollution has reduced.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In recent years, there has been increasing interest in detection of aerosols using various optical spectroscopy techniques. [9][10][11][12][13][14][15] However, these methods (see 1.2.SI †) are not often considered as favorable detection systems, mostly owing to low recovery detection limitations, high cost, not real time, etc. 11 To be fully effective, a biological point detection system should be capable of reliably detecting the presence of a potentially dangerous aerosol immediately it reaches the detection site.…”
Section: Introductionmentioning
confidence: 99%